Prosthetic Knee Joint Infection Secondary to Granulicatella adiacens: A Case Report - Edward Lovering; Farhang Alaee; Michelle Bahrain (Case Reports in Infectious Diseases)
Granulicatella adiacens is an uncommon cause of prosthetic joint infection (PJI). Here, we report a case of Granulicatella adiacens prosthetic knee joint infection in a patient who was previously managed for Granulicatella bacteremia 10 months earlier. The infection was managed with a planned two-stage surgical revision and prolonged IV antibiotics. This case underscores the rare pathogenic potential of a typically benign commensal organism, highlighting the importance of considering atypical pathogens in common clinical presentations.